2019
DOI: 10.1098/rspb.2019.1593
|View full text |Cite
|
Sign up to set email alerts
|

Eye pupil signals information gain

Abstract: In conditions of constant illumination, the eye pupil diameter indexes the modulation of arousal state and responds to a large breadth of cognitive processes, including mental effort, attention, surprise, decision processes, decision biases, value beliefs, uncertainty, volatility, exploitation/exploration trade-off, or learning rate. Here, I propose an information theoretic framework that has the potential to explain the ensemble of these findings as reflecting pupillary response to information processing. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 95 publications
(258 reference statements)
13
43
0
Order By: Relevance
“…learning vs. task solving, exploration vs. exploitation, focused attention vs. mind wandering, etc.). In sum, our findings are consistent with theories of arousal-related neuromodulatory systems that propose their engagement in modulating neural processes in an adaptive manner Zénon, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…learning vs. task solving, exploration vs. exploitation, focused attention vs. mind wandering, etc.). In sum, our findings are consistent with theories of arousal-related neuromodulatory systems that propose their engagement in modulating neural processes in an adaptive manner Zénon, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion must be qualified, however, by the relatively weak sensitivity of subject behavior to volatility level. Given that the pupillary response has been shown to be modulated by probabilities and at least qualitatively demonstrates more extended responses to low probability events ( Alamia et al, 2019 ; Qiyuan et al, 1985 ; Zénon, 2019 ), we cannot completely rule out this possibility. Nor can we rule out the possibility that the difference between explore and exploit response was due to anticipated outcome, which prior studies have demonstrated positively modulates pupil diameter ( Cash-Padgett et al, 2018 ; Van Slooten et al, 2018 ; Varazzani et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, open questions remain about the nature of the relationship. Pupil diameter is sensitive to several non-luminance-mediated factors, including uncertainty and surprise ( Alamia et al, 2019 ; Friedman et al, 1973 ; Jepma and Nieuwenhuis, 2011 ; Lavín et al, 2014 ; Nassar et al, 2012 ; Preuschoff, 2011 ; Qiyuan et al, 1985 ; Urai et al, 2017 ; Zénon, 2019 ), as well as mental load or task difficulty ( Alnæs et al, 2014 ; Hess and Polt, 1964 ; Kahneman and Beatty, 1966 ; Wahn et al, 2016 ). Notably, past task designs used to test the relationship between LC-NE-linked activity and exploratory state do not always clearly differentiate states of exploration from these other factors.…”
Section: Discussionmentioning
confidence: 99%
“…This latter approach seems specially promising in view that only a handful of studies investigated the physiological effect of magic (Parris et al, 2009;Danek et al, 2015;Caffaratti et al, 2016). Crucially, a number of physiological signatures have been already related specifically to Bayesian surprise, such as pupil dilation (Zénon, 2019), the P300 evoked related potential in EEG (Mars et al, 2008;Wacongne et al, 2011;Kolossa et al, 2012;Kopp et al, 2016) and fMRI responses in the dorsal anterior cingulate cortex (Ide et al, 2013;O'Reilly et al, 2013;Schwartenbeck et al, 2016). This previous empirical work and theoretical framework allows a variety of hypothesis-driven physiological studies of magic tricks, such as the parametric modulation of neural signals as a function of surprise, contextual information and attentional control.…”
Section: Discussionmentioning
confidence: 99%